Կովկասի հայոց բարեգործական ընկերության պատմությունից (1881 թ.– 1914 թ. սեպտեմբեր) - Ադամյան, Նինետա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В ноябре 1881 г. в Тифлисе, благодаря усилиям видных армянских деятелей Баграта Навасардяна, Габриэла Сундукяна, Сенекерима Арцруни, а также Александра Манташянца, Аветика Езекяна, Ованеса Читахова, Аршака Нахапеткяна и др., было основано Кавказское армянское благотворительное общество (КАБО), которое просуществовало до 1921 г. In November, 1881 thanks to the efforts of the prominent Armenian figures – Bagrat Navasardyan, Gabriel Sundukyan, Senekerim Artsruni, as well as Alexander Mantashyants, Avetik Yezekyan, Hovhannes Chitakhov, Arshak Nakhapetkyan and others, the Armenian Benevolent Society of the Caucasus (ABSC) was founded, which existed until 1921.
Keywords: Armenian Benevolent Fund